FREE TIME AS A DETERMINANT OF ECONOMIC DEVELOPMENT CULTURAL CONTEXT - Agata Niemczyk (Polityki Europejskie, Finanse i Marketing)
The article presents the results of the analysis of the interplay between free time and economic development of a region. Since culture is one of the ways of spending one’s free time, the main objective of this article is the presentation of interdependencies between the level of development of the cultural function of a region and the level of its economic development. Published GUS data referring to Polish voivodships were used and their availability set the timeframe of the research which covered the years 2005 – 2013. Theoretical considerations describing the relation between free time and economic development were preceded by empirical analyses.